EVALUASI IMPLEMENTASI PROGRAM JAMINAN KESEHATAN NASIONAL (JKN) DALAM MENINGKATKAN ASUHAN PERSALINAN DI RSUD TANJUNG BATU KUNDUR - Norhadianty, Sari; Dwi Anjani, Arum (Universitas Batam, 2025)
Based on the initial survey conducted by researchers, there were still some pregnant women who did not know that they had National Health Insurance (JKN), they only found out that they had National Health Insurance (JKN) by checking in the registration section, most of this was due to a lack of information. from the RT or local village officials. Objective: To find out the evaluation of the implementation of the National Health Insurance (JKN) program in improving maternity care. Quantitative research method, approach with a cross sectional design, January-August 2024. Place at RSUD Tanjung Batu Kundur. Research population of mothers giving birth. The sampling technique in this research is Accidental Sampling. Analysis using Chi-Square. Results: Respondents with good knowledge were 7 respondents (21.9%) and with sufficient knowledge were 20 respondents (62.5%), with poor knowledge were 5 respondents (15.6%), those with JKN were 18 respondents (43.8%). ), Those who do not have JKN amounted to 14 respondents (56.3%). It is known that the Sig. (2-tailed) between Knowledge (X) and JKN Ownership (Y) is 0.098>0.05. The conclusion is that there is no significant correlation between the knowledge variable and the JKN ownership variable.